Analisis Melodi Dan Syair Lagu Buku Zinunö No. 257 Da Ma’ohe Khöu Zumange Di BNKP Tarutung Kota - Gita Lestari Lase (IAKN Tarutung, 2021)
The purpose of this study was to clearly determine the background and melody structure of the song Da Ma'oheKhöuZumange. The song Da Ma'oheKhöuZumange is a traditional Nias nuanced song with the theme of the song offered in the Newest BNKP Zinunö Book. This research uses descriptive qualitative research methods. The work process carried out is literature study, observation, and interviews. The research was carried out by collecting information through field research to obtain results that were processed into definite data. The meaning of the lyrics of the song Da Ma'oheKhöuZumange is an affirmation that what is offered to God actually comes from God.In this song it is also stated that the offering does not only talk about money and materials, but also life in totality. This song has a 4/4 measure with a tempo of 74 MM with the basic tone D = Do, consisting of 16 bars and two phrases. The rim is a, a, a, b. With the chord progressions moving from I, IV, IIIm, VIm, V, I.In the Da Ma'oheKhöuZumange song there are authentic cadens because the chords move from the dominant chord (V) to the tonica chord (I).The ambitus of this song is Fis-B. The tempo in completing this song is 51.8 secondsKeywords: Melody, analysis, and Song lyrics of Da Ma'oheKhöu Zumange